1.
а)
х²/(х²-у²) * (х-у)/х = х²/(х-у)(х+у) * (х-у)/х = х/(х+у),
б)
а/(3а+3в) : а²/(а²-в²) = а/(3*(а+в)) : а²/(а-в)(а+в) =
= а/(3*(а+в)) * (а-в)(а+в)/а² = (а-в)/3а,
в)
(-2с³/у)⁵ = -32с¹⁵/у⁵
г)
х/у² * 4ху = 4х²/у
2.
( у/(у-х) - (у-х)/у ) * (у-х)/х =
= ( у² - (у-х)²) / (у-х)у ) * (у-х)/х =
= ( у²-у²+2ху-х² ) / (у-х)у ) * (у-х)/х =
= х(2у-х) / (у-х)у ) * (у-х)/х = (2у-х) / у,
3.
(2х-4)/(х²+12х+36) : (8х-16)/(х²-36) =
= 2*(х-2)/(х+6)² : 8*(х-2)/(х-6)(х+6) =
= 2*(х-2)/(х+6)² : (х-6)(х+6)/8*(х-2) =
= (х-6) / 2*(х+6),
при х = 1,5:
(1,5-6) / 2*(1,5+6) = -4,5 / (2*7,5) = -4,5 / 15 = -3/10 (или -0,3)
4.
( а-8 + 32а/(а-8) ) * ( 8+а - 32а/(8+а) ) =
= [ ( (а-8)²+32а )/(а - 8) ] * [ ( (8+а)²-32а)/(8+а) ] =
= (а²-16а+64+32а)/(а-8) * (64+16а+а²-32а)/(8+а) =
= (а²+16а+64)/(а-8) * (а²-16а+64)/(8+а) =
= (а+8)²/(а-8) * (а-8)²/(8+а) =
= (а + 8)(а - 8) = а² - 64
рукописный вариант:
⇅⇅⇅⇅
1. a) (y-6)²=y²-12y+36
b) (7x+2)²=49x²+28x+4
в) (4c-1)(4c+1)=16c²-1
г) (2a+3b)(2a-3b)=4a²-9b²
2. a) (x-3)(x-7)-2x(3x-5)=x²-7x-3x+21-6x²+10=-5x²-10x+31
б) 4a(a-5)-(a-4)²=4a²-20a-a²-8a+16=3a²-28a+16
в) 2(m+1)²-4m=2(m²+2m+1)-4m=2m²+4m+2-4m=2m²+2
г) (a-8)²-(64+2a)=a²-16a+64-64-2a=a2-18a
3. (2-x)²-x(x+1,5)=4
4-4x+x²-x²-1,5x=4
-5,5x=4-4
-5,5x=0
x=0/-5,5
x=0
4.
а) (y²– 2а) (2а + y²)=y⁴-4a²
б) (3х² + х)²=6x⁴+6x³+x²
в) (2 + m)² (2 – m)²=(4+4m+m²)(4-4m+m²)=16-8m²+m⁴
5. Упростите выражение
(у² – 2у)² – у²(у + 3)(у – 3) + 2у(2у² + 5)=y⁴-4y³+4y²-y²(y²-9)+4y³+10y=13y²+10y
вот все решение, если что-то непонятно спрашивай